How to efficiently tune the biradicaloid nature of acenes by chemical doping with boron and nitrogen. Issue 29 (12th July 2017) - Pinheiro, Max; Ferrão, Luiz F. A.; Bettanin, Fernanda; Aquino, Adélia J. A.; Machado, Francisco B. C.; Lischka, Hans
Abstract : Strong modulation of the biradical character of acenes with dopant positions is demonstrated by tracking the unpaired electron densities. Abstract : Acenes are fascinating polyaromatic compounds that combine impressive semiconductor properties with an open-shell character by varying their molecular sizes. However, the increasing chemical instabilities related to their biradicaloid structures pose a great challenge for synthetic chemistry. Modifying the π-bond topology through chemical doping allows modulation of the electronic properties of graphene-related materials. In spite of the practical importance of these techniques, remarkably little is known about the basic question – the extent of the radical character created or quenched thereby. In this work, we report a high-level computational study on two acene oligomers doubly-doped with boron and nitrogen, respectively. These calculations demonstrate precisely which the chemical route is in order to either quench or enhance the radical character. Moving the dopants from the terminal rings to the central ones leads to a remarkable variation in the biradicaloid character (and thereby also in the chemical stability). This effect is related to a π-charge transfer involving the dopants and the radical carbon centers at the zigzag edges. This study also provides specific guidelines for a rational design of large polyaromatic compounds with enhanced chemical stability.